A Review of Wireless Multimedia Sensor Network and existing Routing Protocols - Deb, Moumita; Choudhury, Abantika (International Journal of Computer Sciences and Engineering, 2025)
Growing popularity of multimedia data give birth to a new field in sensor network, called wireless multimedia sensor network (WMSN) that can handle multimedia data along with the normal scalar data. Advances in CMOS (Complementary Metal Oxide Semiconductor), help sensor nodes to gather, process and transport multimedia data along with the textual data. But resource constraint nature of sensor network makes the implementation of multimedia sensor network very difficult and traditional approaches fail to deal with the consequences generated from transmitting multimedia data. Yet its popularity is increasing as it has potential civilian and military applications. Multimedia data has stringent Quality of Service requirement (QoS) such as delay, jitter, packet loss rate, energy etc. and to satisfy those criteria, routing protocols needs to modify. The critical problem to handle by the routing protocols are managing the energy while maintaining QoS requirement and handling the unreliable error prone communication medium. Here we have studied existing routing protocols used for multimedia data transmission and figure out some problems need to be addressed for future research.